Biomechanical evaluation of implants with different surfaces: analysis of stability coefficient and removal torque in rabbits - Rodríguez, Arminda (2025)
Objective: Evaluate the biomechanical behavior of three implant brands with different surfaces by comparing stability parameters during placement and removal. Materials and Methods: An experimental study was conducted with 8 rabbits, in which 21 implants from three different brands were placed: ML Implant System®, Roster Dent®, and Biomet 3i® Osseotite. Seven implants of each brand were placed in each femur, and resonance frequency analysis was performed to measure the initial stability coefficient (initial ISQ). At 60 days, the final stability coefficient of the implants was measured. To measure removal torque, the implants were fixed in a press, and a Mark-10 precision digital torque wrench was used. Implants were removed by reverse rotation, recording the peak removal torque value. Results: Regarding initial-stage stability, the Roster Dent® and ML Implant System® groups showed higher values than the Biomet 3i® group, although differences were not significant (p=0.82). However, the ML Implant System® group showed lower final-stage stability (p=0.04). No statistically significant difference was observed between insertion and removal torque. Intergroup differences in removal torque were also non-significant. Conclusions: The studied implant systems demonstrated similar behavior during biomechanical insertion and removal torque testing. Differences were noted among all brands when comparing initial and final resonance frequency analyses (mechanical stability vs. biological stability). The ML Implant System® group showed a lower ISQ in the final stage.